Critical Analysis of Plagiarism in Bahaullah’s Teachings - Ayaz, Muhammad; Anwar, Sohail (Journal of Islamic and Religious Studies, 2016)
The main objective of human life is to get closeness to Allah Almighty and to worship Him. For this purpose thousands of prophets were sent to guide the people on the right path. Other prophets were sent for a specific nation, limited time and area. At the end prophet Muhammad (SAW) was sent by Allah as the last and universal prophet. On the other hand it is also a bitter fact that in all the times and area there are some people who do not follow, become hurdles and even misguide the others (for their cheap worldly benefits). ╓ussain Alī Mazandrānī is one of those false and fake people. He wrote a book, namely, Kitāb-e-Aqdas and claims it to be the word of Allah, revealed on him, while the fact is that Qur’ānic commands (orders) have been presented in his book according to the will and convenience of people. In some places the very text of the Holy Qur’ān has been copied. The given article discovers this plagiarism and critically analysis the commands written in Kitāb-e-Aqdas in the light of the Holy Qur’ān. And this has been proved with arguments that the Holy Qur’ān is the word of Allah, which is completely safe, while Kitāb-e-Aqdas is the outcome of human efforts written by ╓ussain Alī. Hence it is unsafe and not free from mistakes.